Análise de processos de texturação para células solares N-PERC com emissor P+ formado por radiação laser - Lopes, Bruno Krever (2024)
This dissertation focuses on the processing and analysis of boron-doped emitters, formed through laser diffusion and selective texture etching. Selective texture etching involves creating planar regions where boron is diffused and textured surfaces in regions without boron. The samples were produced through three processes: A, B, and C. In process A or selective texture etching, boron diffusion was carried out before the anisotropic etching, necessary to form a textured surface. To this process, four texturing times were used. In process B, texture etching was performed before laser boron diffusion. In process C, only laser processing was done to assess the damage caused to the silicon wafer. The samples were analyzed through optical microscopy, scanning electron microscopy, sheet resistance measurement (RSQ), reflectance measurement, and minority carrier lifetime (). Samples developed through process B (control process) exhibited RSQ values in the range of 26–28 Ω/sq, while samples developed through process A (process with selective texturing) showed an increase in RSQ values, ranging from 53 to 60 Ω/sq. Regarding reflectance analysis, all wafers subjected to process A had higher reflectance values compared to those subjected to process B, with a 4% difference in the average weighted reflectance even for samples produced with the same 60-minute etching period. When analyzing the percentage difference in minority carrier lifetime values between regions subjected to laser diffusion (fingers) and regions without diffusion (between fingers), a more significant decrease in  was noted in the samples processed through the control method with pre-laser etching (process B). These results indicate that the use of an anisotropic KOH etching after laser diffusion partially reduces the damage in the silicon generated in the processing.